1998
DOI: 10.1128/jvi.72.7.6271-6276.1998
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hypervariable Region 1 of Hepatitis C Virus in Primary Infection

Abstract: The hypervariable region 1 (HVR-1) of the putative envelope encoding E2 region of hepatitis C virus (HCV) RNA was analyzed in sequential samples from three patients with acute type C hepatitis infected from different sources to address (i) the dynamics of intrahost HCV variability during the primary infection and (ii) the role of host selective pressure in driving viral genetic evolution. HVR-1 sequences from 20 clones per each point in time were analyzed after amplification, cloning, and purification of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Indeed, epitopes are present in some HVR1 sequences that induce the formation of humoral antibodies, 26,[28][29][30][31] and neutralizing activity has been shown with antibodies directed against particular HVR1 sequences. 7,27,32,33 The observed evolution of HVR1 also could be caused by the activity of HCV-specific CTLs. In chimpanzees that resolved their HCV infection, intrahepatic HCV-specific CTL responses were initially detected at 5 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, epitopes are present in some HVR1 sequences that induce the formation of humoral antibodies, 26,[28][29][30][31] and neutralizing activity has been shown with antibodies directed against particular HVR1 sequences. 7,27,32,33 The observed evolution of HVR1 also could be caused by the activity of HCV-specific CTLs. In chimpanzees that resolved their HCV infection, intrahepatic HCV-specific CTL responses were initially detected at 5 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…HVR1 can encode peptides that generate neutralizing antibodies against HCV, and host immune defenses are probably important factors in driving its evolution. 7,8 In this study of transfusion-transmitted HCV, we analyzed HVR1 in donor-recipient pairs as a function of the time elapsed between the date of transmission and the sample collection date. To determine the time intervals over which this particular genomic region remained unchanged, we studied within-recipient changes in HVR1 in serial specimens.…”
mentioning
confidence: 99%
“…41 Analysis of anti-HVR1 responses in subjects with acute HCV infection revealed that the vigor and cross-reactivity of HVR1 antibody responses were significantly higher in patients with chronic compared with those with acute infection, regardless of their clinical outcome. Because, on primary infection HCV is propagated as a homogeneous population of virions in which a single or a very small number of HVR1 sequences are present, 42 it is likely that cross-reactive immune responses are progressively generated as new HVR1 variants are selected during the course of infection. However, in some of the patients with acute hepatitis cross-reactive, antibodies could be detected early after clinical onset, when only a single molecular species was detectable in the serum, suggesting that cross-reactive anti-HVR1 responses may appear early in the course of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…49 These types of mutation mostly occur at the outer membrane protein, ie, at the spike protein. 50 These types of mutation increase the sustainability of the HCoVs, by ensuring their escape from both the cell-mediated and humoral immune responses. 51 Despite this, spike proteins have the most potential as a target for vaccine design because of their ability to induce a faster and longer-term mucosal immune response than that of the other proteins 52 and for this reason, has gained much popularity with researchers.…”
Section: B Cell Epitope Identificationmentioning
confidence: 99%